2012
DOI: 10.1371/journal.pone.0050213
|View full text |Cite
|
Sign up to set email alerts
|

Independent and Joint Effects of Prenatal Zinc and Vitamin A Deficiencies on Birthweight in Rural Sidama, Southern Ethiopia: Prospective Cohort Study

Abstract: BackgroundThe effects of prenatal Zinc Deficiency (ZD) and Vitamin A Deficiency (VAD) on birthweight are controversial and their interaction has not been investigated.ObjectiveTo assess the independent and interaction effects of prenatal zinc and vitamin A deficiencies on birthweight in rural Sidama, Southern Ethiopia.MethodologyA community-based prospective cohort study design was employed. Six hundred fifty pregnant women in their second or third trimester were randomly selected and their serum zinc and reti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
27
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 26 publications
6
27
1
Order By: Relevance
“…In particular, birth weight is not known for rural babies and such community-based studies focusing on rural populations find higher incidence of LBW than facility-based studies [13], [14]. For instance, recent community based studies in eastern and southern Ethiopia found higher incidence of LBW of 28% and 17% respectively [15], [16]. In the 2011 Ethiopian Demographic and Health Survey, a nationally representative population-based sample, reported that 21% of all live births in rural Ethiopia in the five years preceding the survey were very small in size, as reported subjectively by the mother [17].…”
Section: Discussionmentioning
confidence: 99%
“…In particular, birth weight is not known for rural babies and such community-based studies focusing on rural populations find higher incidence of LBW than facility-based studies [13], [14]. For instance, recent community based studies in eastern and southern Ethiopia found higher incidence of LBW of 28% and 17% respectively [15], [16]. In the 2011 Ethiopian Demographic and Health Survey, a nationally representative population-based sample, reported that 21% of all live births in rural Ethiopia in the five years preceding the survey were very small in size, as reported subjectively by the mother [17].…”
Section: Discussionmentioning
confidence: 99%
“…Again, we excluded 100 duplicate records and finally we left with 19 records. After assessing the full texts of the 19 records for their eligibility, 6 records [21][22][23][24][25][26] were further excluded by the exclusion criteria. Finally, 13 studies, 7 for pregnant women [15,[27][28][29][30][31][32] and 6 for children [11,[33][34][35][36][37], were found to be eligible for this systematic review and meta-analysis ( Fig.…”
Section: Study Selectionmentioning
confidence: 99%
“…A clinical trial reported that daily Zn supplementation in women with relatively low plasma Zn concentrations at 19 weeks gestation is associated with greater infant birth weights and head circumferences. 112 Conversely, studies using blood samples collected at birth or in late pregnancy have produced inconsistent results, with eight studies 78,114119 showing no association and three studies 120122 observing an increased risk between maternal serum Zn levels and risk of delivering LBW infants.…”
Section: Effects Of Environmental Exposures On Fetal and Childhoodmentioning
confidence: 99%
“…Toxic metals reaching the fetus could impair or alter the uterine environment and dysregulate the fetal epigenome, given that the embryo and fetus are highly susceptible to epigenetic dysregulation by environmental pollutants, 115,119 may affect gene expression and enzyme activity in placental trophoblast cells, 124 act as endocrine disruptors, 123,135138 and/or develop persistent vulnerabilities in immune system function that would affect fetal development. 138,139 Trace minerals could lead to adverse health effects at too high levels.…”
Section: Effects Of Environmental Exposures On Fetal and Childhoodmentioning
confidence: 99%